Financing Social Entrepreneurship through Crowdfunding in Morocco: Proposal for a Conceptual Model - MEGHRAOUI , Niama; AÏT LEMQEDDEM , Hamid (Revue Internationale du Chercheur, 2024)
Over the years, crowdfunding has become a central pillar in the social entrepreneurship ecosystem. It provides a crucial channel for financing in line with the principles of the social and solidarity economy and boosts community mobilization. Crowdfunding offers unique benefits to social entrepreneurs and catalyzes the demonstration and commercialization of projects with significant social impact. In Morocco, the introduction of Law No. 15-18 on collaborative financing in 2021 marks a decisive turning point. This legislative text promotes inclusion and financial transparency for social project leaders while protecting their interests. This work, initiated by a documentary exploration followed by interviews with ten Moroccan social entrepreneurs, allowed us to draw up an initial overview of the interactions between social entrepreneurship and crowdfunding mechanisms in the Moroccan context and build a solid conceptual model. This article reveals a dynamic ecosystem in which crowdfunding and Moroccan regulation interact, generating beneficial effects on social entrepreneurship.